Immigrant workers in the meat industry during COVID-19: comparing governmental protection in Germany, the Netherlands, and the USA - Nora Gottlieb; Ingrid Jungwirth; Marius Glassner; Tesseltje de Lange; Sandra Mantu; Linda Forst (Globalization and Health)
Abstract The meat industry showcases the precarity of employment arrangements as part of broader global economic liberalization. In many countries, its workforce consists mostly of precariously employed immigrant and resident foreign-born workers. Categorized as “essential workers”, they worked throughout the COVID-19 pandemic, while facing high infection risk. Using case-studies in three country contexts – Illinois/USA, the Netherlands, and North Rhine-Westphalia/Germany – we analyzed policy documents, investigative reports, publicly available data, and informal expert consultation to examine structural causes of protection gaps for workers in the meat industry as well as facilitators and barriers to improving occupational safety and health. The Framework Method was applied to systematize and compare the overall data. Our analysis yields two key findings: First, immigrant workers in the meat industry face similar structural conditions across country contexts, with intersecting immigration- and employment-related precarity, generating gaps in social and health protection and deficiencies in the realization of theoretically held rights. Second, as policy responses to SARS-CoV-2 outbreaks varied, our case-studies showcase fundamentally different approaches to state responsibility for worker wellbeing as part of food supply chain (FSC) governance. The sacrificial-worker approach, observed in Illinois/USA, prioritized industry interests over worker and public health. In the Netherlands, a passive government delegated responsibilities to industry actors who forestalled systemic change through ad hoc adjustments, leaving the core problem of workers’ precarity intact. In Germany, the government leveraged the COVID-19 pandemic as a catalyst for change by enforcing a ban on subcontracting workers in the meat industry, with the potential to fundamentally shift industrial relations and thus address the root causes of worker precarity. Our results highlight economic liberalization and related worker precarity as central determinants of health inequities; and they underscore the imperative for more equitable social and health protection of all workers as part of FSC governance, and as part of food systems transformation for sustainability.